Audit, Gender, and Taxes: The Interplay Between Female CEOs and Big Four Auditors - Nurul Fitriani; Selma Putri Safira (Jurnal Akuntansi dan Keuangan, 2025)
This research examines the relationship between CEOs’ gender and the presence of top-tier external auditors, specifically those from the Big Four, with corporate tax avoidance practices in Indonesia. Based on agency theory and considering Indonesia's unique institutional landscape, where women remain underrepresented in executive leadership, the study explores how gender and audit quality influence corporate financial behavior. Using 1,001 firm-year observations from publicly listed Indonesian companies between 2021 and 2023, regression analysis tested the effects of female leadership and Big Four auditors on tax strategies. Findings reveal that companies led by female CEOs tend to engage in higher levels of tax avoidance. However, when Big Four auditors are involved, this relationship weakens, demonstrating the role of high-quality audits in curbing managerial discretion and enhancing accountability. The study offers fresh insights into corporate governance in emerging markets.